Disordered eating concerns, behaviors, and severity in young adults clustered by anxiety and depression - Kaitlyn M. Eck; Carol Byrd‐Bredbenner (Brain and Behavior, 2021)
Abstract Objectives Little is known about how anxiety and depression in combination relate to eating disorder concerns (eating, shape, and weight concern) and behaviors (restraint eating, binge eating, and purging) indicative of eating disorder symptom severity. This study examined links among disordered eating concerns, behaviors, and severity clustered by depression and anxiety. Methods College students (n = 1792) completed a survey comprised of the Generalized Anxiety Disorder Scale (GAD‐7), 2‐item Patient Health Questionnaire (PHQ‐2) assessing Major Depressive Disorder (MDD), and Eating Disorder Exam Questionnaire (EDE‐Q) assessing concerns and behaviors indicative of disordered eating. Results Cluster analysis yielded four groups: not depressed or anxious to subclinical, moderate, and high depression and anxiety. Analysis of variance (ANOVA) indicated overall eating disorder severity scores increased significantly as GAD and MDD increased, suggesting that as anxiety and depression rise in tandem, disturbed eating severity rises. Results revealed that even at subclinical levels, disordered eating concerns, behaviors, and overall severity scores increase. Discussion Future interventions aiming to reduce disordered eating in young adults may be strengthened by incorporating depression and anxiety management strategies. A screening for subclinical anxiety and depression (Mixed Anxiety and Depression Disorder [MADD]) may be helpful in providing early intervention to resolve disordered eating behaviors before they become entrenched.